2022
DOI: 10.3233/jpd-212934
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Induced Pluripotent Stem Cell-Derived Dopaminergic Neurospheres for Clinical Application

Abstract: Background: Pluripotent stem cell (PSC)-derived dopaminergic (DA) neurons are an expected source of cell therapy for Parkinson’s disease. The transplantation of cell aggregates or neurospheres, instead of a single cell suspension has several advantages, such as keeping the 3D structure of the donor cells and ease of handling. For this PSC-based therapy to become a widely available treatment, cryopreservation of the final product is critical in the manufacturing process. However, cryopreserving cell aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…By optimizing conversion and culture conditions, we successfully generated BFCNs that rapidly develop Aβ42 and pTau pathologies within 13–21 days, a timeframe considerably shorter than the typical 50-day period 28 . Additionally, these BFCNs were freezable, with freezing/thawing viability comparable to or higher than the iPSC-derived fetal neurons 31 , which significantly facilitates their storage, transportation, and application. This accelerated onset of natural endogenous neuropathology enhances the efficiency and reliability of evaluating potential AD therapeutics, offering a more accessible and dependable platform for testing.…”
Section: Discussionmentioning
confidence: 99%
“…By optimizing conversion and culture conditions, we successfully generated BFCNs that rapidly develop Aβ42 and pTau pathologies within 13–21 days, a timeframe considerably shorter than the typical 50-day period 28 . Additionally, these BFCNs were freezable, with freezing/thawing viability comparable to or higher than the iPSC-derived fetal neurons 31 , which significantly facilitates their storage, transportation, and application. This accelerated onset of natural endogenous neuropathology enhances the efficiency and reliability of evaluating potential AD therapeutics, offering a more accessible and dependable platform for testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported protocols for cryopreserving near-mature PSC-derived neurons with fully identified neuronal properties after thawing. Most studies have demonstrated NSC or progenitor-stage cell storage for ~15 days of differentiation, which still require another 2–3 weeks for neural patterning or maturation [ 18 , 19 ]. Here, we demonstrate an efficient protocol to cryopreserve MN EBs for 32 days using Stem-CellBanker with a sphere size of <300 µM and ROCKi addition.…”
Section: Discussionmentioning
confidence: 99%
“…The cryopreservation of neuronal cells with high viability that retains their properties is difficult. Although there have been current studies that have reported the cryopreservation of iPSC-derived dopaminergic progenitors for Parkinson’s disease transplantation [ 18 , 19 , 20 ], only a few have achieved MN or MNP cryopreservation but without further functional analysis [ 21 ]. Moreover, most reports demonstrated that neuronal progenitors or stem cells are frozen within 10–20 days of differentiation instead of late-stage premature neurons (>30 days) [ 18 , 19 , 20 ], requiring additional maturation to recapitulate disease phenotypes for model applications.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell banks increase the availability and ensures the quality of the cell products, while reducing the time to administer the therapy ( 168 ). Not only iPSCs can be banked, but also their derivatives including iMSCs ( 169 ) and some types of differentiated cells ( 170 ), as well as their secretomes ( 171 ). However, it is important to note that allogeneic therapy also has its own limitations, highlighting the risk of immunological rejection ( 167 ).…”
Section: Applications Of Ipscs In Companion Animalsmentioning
confidence: 99%